Medication adherence supported by mHealth and NFC. (2021) - Orcioni, Simone; Pellegrini, Roberto; Seepold, Ralf; Gaiduk, Maksym; Madrid, Natividad Martínez; Conti, Massimo
Abstract: The present work proposes the use of modern ICT technologies such as smartphones, NFCs, internet, and web technologies, to help patients in carrying out their therapies. The implemented system provides a calendar with a reminder of the assumptions, ensures the drug identification through NFC, allows remote assistance from healthcare staff and family members to check and manage the therapy in real-time. The system also provides centralized information on the patient's therapeutic situation, helpful in choosing new compatible therapies.